VITAMIN-D STATUS AT BREAST CANCER DIAGNOSIS: CORRELATION WITH SOCIAL AND ENVIRONMENTAL FACTORS AND DIETRY INTAKE - Imtiaz, Saba; Siddiqui, Neelam (Journal of Ayub Medical College Abbottabad, 2014)
Background: Serum levels of vitamin-D are low in breast cancer patients. Vitamin-D levels have inverse correlations with postmenopausal state, obesity, poor sun exposure and low intake of vitamin-D rich diet. The objective of this study was to quantify levels of vitamin-D in serum to determine the degree of vitamin-D deficiency in breast cancer patients compared with age matched controls and to observe the association between serum 25-OH vitamin-D levels and personal and social parameters, BMI, amount of sun exposure and dietary intake. Methods: In this cross-sectional analytical study all newly diagnosed breast cancer female patients were recruited into the study over a period of 6 months. Age matched healthy females were also recruited as a control group. Personal and social data was documented on to a pro forma. Sun exposure was determined by mid-day exposure to direct sunlight. Serum 25-OHD levels were studied by ELISA technique on the blood samples. The dietary information was collected by recall over the last 1 year. Results: Vitamin-D deficiency was found in 99% breast cancer females and 90% in healthy females. Mean serum vitamin-D level was 9.6±5 ng/ml and 15.2±10 ng/ml for cases and control group respectively. All breast cancer and 95% healthy females with BMI >30 were found to be vitamin-D deficient. Menopausal state, parity, parda (veil) observation, area of living and sun exposure did not affect vitamin-D status in either group. Egg, fish and cheese intake revealed correlation with vitamin-D deficiency. Forty percent healthy females were found to have deficient serum vitamin-D levels despite being on supplement. Conclusion: Vitamin-D deficiency was highly prevalent among breast cancer females. Serum 25 OHD levels exhibited an inverse correlation with high body mass index and vitamin-D rich diet. Keywords: Vitamin-D deficiency, breast cancer, 25-OHD, sun exposure, body mass index